Repeated megafloods from glacial Lake Vitim, Siberia, to the Arctic Ocean over the past 60, 000 years. (1st May 2018) - Margold, Martin; Jansen, John D.; Codilean, Alexandru T.; Preusser, Frank; Gurinov, Artem L.; Fujioka, Toshiyuki; Fink, David
Abstract: Cataclysmic outburst floods transformed landscapes and caused abrupt climate change during the last deglaciation. Whether such events have also characterized previous deglaciations is not known. Arctic marine cores hint at megafloods prior to Oxygen Isotope Stage (OIS) 2, but the overprint of successive glaciations means that geomorphological traces of ancient floods remain scarce in Eurasia and North America. Here we present the first well-constrained terrestrial megaflood record to be linked with Arctic archives. Based on cosmogenic-nuclide exposure dating and optically stimulated luminescence dating applied to glacial-lake sediments, a 300-m deep bedrock spillway, and giant eddy-bars > 200-m high, we reconstruct a history of cataclysmic outburst floods from glacial Lake Vitim, Siberia, to the Arctic Ocean over the past 60, 000-years. Three megafloods have reflected the rhythm of Eurasian glaciations, leaving traces that stretch more than 3500 km to the Lena Delta. The first flood was coincident with deglaciation from OIS-4 and the largest meltwater spike in Arctic marine-cores within the past 100, 000 years (isotope-event 3.31 at 55.5 ka). The second flood marked the lead up to the local Last Glacial Maximum, and the third flood occurred during the last deglaciation. This final 3000 km 3 megaflood stands as one of the largest freshwater floods ever documented, with peak discharge of 4.0–6.5 million m 3 s −1, mean flow depths of 120–150 m, and average flow velocities up to 21 m s −1 . Highlights: History of megascale outburst floods from glacial Lake Vitim, Siberia, reconstructed. Three megafloods to the Arctic Ocean occurred over the past 60, 000-years. Final 3000 km 3 megaflood is one of the largest freshwater floods ever documented.